Some Common Fixed-Point Theorems in Fuzzy Metric Space in the Context of Single and Set-Valued Mapping via OWC Mapping - Yadav, Sushma; Wadhwa, Kamal; Tiwari, Rashmi (Communications in Mathematics and Applications, 2025)
This study aims to construct some common theorems in FMS for two pairs of single and set-valued OCM mappings that satisfy integral type contractive requirements. Our findings expand upon and generalize a number of related findings from previous research for independent of continuity and completeness.
Keywords: Fuzzy Metric Space (FMS); Common Fixed Point (CFP); Occasionally Weakly Compatible Mapping (OWC); Single Valued Mapping (SVM); Set-Valued Mapping (SEVM)